Mediação cultural : estudo e prática a partir das informações presentes nas esculturas religiosas, na documentação e no ambiente virtual no Museu de Arte Sacra de Laranjeiras/SE - Santos, Maria de Lourdes dos (2019)
The present study proposes to contribute with the process of cultural mediation, in the context of Information Science, inserted in the museum space. Aiming to measure actions of cultural mediation through the research on the imaginary of the long-term exhibition of the Museum of Sacred Art of Laranjeiras (MASL); with the objectives of equipping the Museum with instruments that promote mediation between the object and the user; create a photographic and documentary catalog, as well as create a blog, in order to develop the research and give greater visibility to the institution and its collection. Such information, as well as the photographic collection allied to documentary research and the use of ICT, will be part of the process of cultural mediation between the Museum and its public. It is intended to support a theoretical and technical proposal of exploratory research of each sculptural representation, under the iconographic, artistic and historical vision, in the light of the production and use of cultural mediation, in order to fill the existing information gaps. Its relevance originates from the fact that through the study of the object, the process of mediation can be enabled and through this, to carry out the dissemination of information and the management of knowledge. To compose this scenario, it became necessary to know from the construction of the political, economic and religious history of the city reflected through its patrimonial assets, comprised between the eighteenth and mid twentieth centuries, a time that marks the beginning of its apogee and of its decline. In the scope of the research, it composes a historiographic identification, according to artistic styles, origin and other relevant instruments of analysis with the intention of making available instruments that reveal the documentary meaning of the collection, in a rupture in the currently used approach.Following this structure, the cultural mediation of information is effectively the action that will allow access and interaction between the product and its target audience. A qualitative approach was adopted, combining the contemporary and interactive technology, through a blog and a physical instrument in form, of a documentary catalog of the imaginaries promoting the necessary conditions for the dissemination to be a reality through the means and practices of cultural mediation.